USE OF RITUXIMAB IN AUTOIMMUNE DISEASES: NEW ASPECTS - Dmitry Evgenyevich Karateyev (Современная ревматология)
It has been noted that off-label indication for Rituximab (RTX) in rheumatological care indubitably requires its confirmation in the randomized clinical trials. A particular cautious approach should be taken in extending the indications for therapy with gene-engineering biologicals because of the intricacy and interaction of different immunoregulatory mechanisms. Nonetheless, it is stated that much clinical experience with RTX used in most severely ill therapy-resistant patients may serve as a basis for its prescription in a number of most complex inflammatory rheumatic diseases (RDs). There is new evidence for the use of RTX in various RDs differing in their clinical picture, course, and pathogenesis, such as spondyloarthritis, systemic lupus erythematosus, systemic vasculitis.